Rare Case of Bladder Endometriosis in a Post-hysterectomy Patient - Rajasi Kane Sengupta; Saunitra Inamdar; Surekha Tayade (Journal of Clinical and Diagnostic Research, 2023)
Bladder endometriosis, a rare but well-known condition with a high risk of morbidity, affects the bladder. A 43-year-old woman presented with a history of recurrent cyclical discomfort during urination. The patient had undergone a non descent vaginal hysterectomy to address the same symptom. Upon examination, a nodule was discovered between the bladder and vaginal vault. The diagnosis of bladder endometriosis was confirmed through cystoscopy and an Magnetic Resonance Imaging (MRI). The nodule was removed via transurethal resection, and histology confirmed it as endometriosis. After 12 months of follow-up, the patient's postoperative symptoms had completely resolved. Hormonal therapy was initiated, and there were no residual urinary symptoms, chronic pain, or cyclical pain. Women reporting urinary symptoms, particularly those with a history of pelvic surgery, should undergo evaluation for bladder endometriosis. The diagnosis of bladder endometriosis should be considered in women experiencing dysuria and bladder discomfort. A high index of suspicion is required to establish the diagnosis.